An Examination of Email Fraudsters` Modus Operandi - Maimon, David (Crime & delinquency, 2023)
Focusing on two of the most common deceptive strategies employed by fraudsters, we assess which type of cue—politeness or urgency—is more likely to result in an email fraud attempt. We also examine whether these cues are mutually exclusive and consistent throughout the progression of a fraud attempt. To answer our research questions, we posted “for-sale” advertisements on classified-advertisement websites and interacted with fraudsters who responded to our advertisements. Findings reveal that fraud attempts are more likely to follow probe emails that include cues of urgency than cues of politeness. Moreover, although the majority of fraudsters’ probe emails include deceptive cues of either politeness or urgency, the majority of subsequent emails include deceptive cues of both politeness and urgency.